Quantitative Evaluation of Macro and Micronutrients in Averrhoa bilimbi, Mimusops elengi and Carissa carandas Fruits of Bangladesh - Chandra, Liton; Nazmul Islam, A.B.M.; Khatun, Amina; Matiar Rahman, Md.; Kudrat-E-Zahan, Md.; Abdul Mannan, Md.; Nasiruddin (Asian Journal of Chemistry, 2020)
In present study, a quantitative evaluation of macro and micronutrients in Averrhoa bilimbi, Mimusops elengi and Carissa carandas tropical fruits have been presented. Concentration of the nutrients namely calcium, chromium, manganese, iron, nickel, zinc and two toxic heavy metals cadmium and lead present in the fruits are used as traditional folk medicines in Bangladesh were determined by flame atomic absorption spectrometric method. The concentration of the elements for Averrhoa bilimbi was found to be followed by the order as: Ca (1.98 ppm) > Fe (0.515) > Zn (0.080) > Mn (0.038) > Cr (0.006) > Pb (0.004) > Ni (0.0016) > and Cd (0.0015 ppm), respectively. The order for that of Mimusops elengi was found to be as: Ca (3.175 ppm) > Fe (0.784) > Zn (0.049) > Mn (0.038) > Pb (0.008) > Ni (0.008) > Cd (0.003) > Cr (0.001 ppm) and the same issue for the Carissa carandas was found to be Ca (4.277 ppm) > Fe (0.676) > Zn (0.040) > Mn (0.040) > Pb (0.005) > Ni (0.004) > Cr (0.002) > Cd (0.0009 ppm), respectively. From the obtained results, the analyzed fruits might be an admirable natural source of nutrients Ca, Fe and Zn. Concentration of toxic elements Pb and Cd found to be of very few ppb levels and should not be considered as toxic in consumption by human beings.